Szacowanie prędkości pojazdów na podstawie obrazu z kamery = Estimating vehicle speed based on image from camera - Rajs, Arkadiusz; Goździewska-Nowicka, Agnieszka; Banaszak-Piechowska, Agnieszka; Gospodarczyk, Jacek (Journal of Education, Health and Sport, 2016)
Rajs Arkadiusz, Goździewska-Nowicka Agnieszka, Banaszak-Piechowska Agnieszka, Gospodarczyk Jacek. Szacowanie prędkości pojazdów na podstawie obrazu z kamery = Estimating vehicle speed based on image from camera. Journal of Education, Health and Sport. 2016;6(4):122-126. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49880 http://ojs.ukw.edu.pl/index.php/johs/article/view/3456 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. SZACOWANIE PRĘDKOŚCI POJAZDÓW NA PODSTAWIE OBRAZU Z KAMERY ESTIMATING VEHICLE SPEED BASED ON IMAGE FROM CAMERA dr inż. Arkadiusz Rajs Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckich w Bydgoszczy, Wydział Telekomunikacji, Informatyki i Elektrotechniki, Zakład Teletransmisji, Al. Prof. S. Kaliskiego 7, 85-790 Bydgoszcz, arajs@utp.edu.pl dr Agnieszka Goździewska-Nowicka Uniwersytet Technologiczno-Przyrodniczy im. Jana i Jędrzeja Śniadeckich w Bydgoszczy, Wydział Zarządzania, Katedra Organizacji i Zarządzania, ul. Fordońska 430, 85-790 Bydgoszcz, Agnieszka.Gozdziewska@utp.edu.pl dr Agnieszka Banaszak-Piechowska Uniwersytet Kazimierza Wielkiego w Bydgoszczy Instytut Fizyki, ul. Weyssenhoffa 11, 85-090 Bydgoszcz, agnb@ukw.edu.pl dr inż. Jacek Gospodarczyk Wyższa Szkoła Gospodarki w Bydgoszczy Instytut Informatyki i Mechatroniki Garbary 2,85-229 Bydgoszcz, jacek.gospodarczyk@byd.pl Streszczenie Praca prezentuje sposób oszacowania prędkości poruszających się pojazdów. Opisano metodę opartą na analizie obrazu oraz przedstawiono wyniki pomiarów. Abstract This Work presents a way to estimate the speed of the moving vehicles. Describes a method based on image analysis, and shows the results of the measurements. Słowa kluczowe: analiza obrazu, prędkość pojazdów, systemy wizyjne. Key words: image analysis, machine vision systems, vehicle speed.